User Acceptance Analysis of My Pertamina Application Using UTAUT Model - Muhamad Bakhar; T. Irfan Fajri; Chevy Herli Sumerli A; Nazaruddin Ahmad; Uli Wildan Nuryanto (SEULANGA SYSTEM PUBLISHER, 2023)
The development of information technology makes the world of business competition increasingly fierce. Where not only private companies and MSMEs take a technological approach but also government agencies and BUMN. One of them is Pertamina, which launched the My Pertamina application and has required the use of the application in purchase transactions for subsidized pertalite and diesel fuel. After the enactment of this provision, many users found problems with its use. obstacles experienced by users, such as application errors when processing transactions or transaction data that is not appropriate, so that the application cannot be used outside Java. This study aims to find out how users accept the application and what variables are affected by using the UTAUT model. Performance Expectation, Effort Expectation, Social Influence, Facilitating Conditions, Behavioral Intention, and Use Behavior are the variables considered in this study. 200 respondents were gathered when researchers distributed questionnaires with many questions regarding factors on a Likert scale. Following data analysis, it was discovered that the variables Performance Expectation, Effort Expectation, and Social Influence all positively influence Behavioral Intention, which in turn positively influences Use Behavior.